Mine Eyes Have Seen the Glory : Religion and the Politics of Race in the Civil War Era and Beyond - Dundas, Steven L. (Book collections on Project MUSE., 2022)
"Mine Eyes Have Seen the Glory is a hard-hitting history of the impact of racism and religion on the political, social, and economic development of the American nation from Jamestown to today, in particular the nefarious effects of slavery on U.S. society and history. Going back to England's rise as a colonial power and its use of slavery in its American colonies, Steven L. Dundas examines how racism and the institution of slavery influenced the political and social structure of the United States, beginning with the writing of the Declaration of Independence and the Constitution. Dundas tackles the debates over the Constitution's three-fifths solution on how to count Black Americans as both property and people, the expansion of the republic and slavery, and the legislation enacted to preserve the Union, including the Missouri Compromise, the Compromise of 1850, and the Kansas-Nebraska Act-as well as their disastrous consequences.Mine Eyes Have Seen the Glory squarely faces how racism and religion influenced individual and societal debates over slavery, Manifest Destiny, secession, and civil war. Dundas deals with the struggle for abolition, emancipation, citizenship, and electoral franchise for Black Americans, and the fierce and often violent rollback following Reconstruction's end, the Civil Rights Movement, and the social and political implications today. Mine Eyes Have Seen the Glory is the story of perpetrators, victims, and bystanders; slaves and slaveholders; preachers, politicians, and propagandists; fire-eaters and firebrands; civil rights leaders and champions of white supremacy; and the ordinary people in the South and the North whose lives were impacted by it all. "--